Reconstruction magnetic resonance neurography in chronic inflammatory demyelinating polyneuropathy. Issue 2 (13th December 2014) - Shibuya, Kazumoto; Sugiyama, Atsuhiko; Ito, Sho‐ichi; Misawa, Sonoko; Sekiguchi, Yukari; Mitsuma, Satsuki; Iwai, Yuta; Watanabe, Keisuke; Shimada, Hitoshi; Kawaguchi, Hiroshi; Suhara, Tetsuya; Yokota, Hajime; et al.
<x xml:space="preserve">Abstract</x> To study distribution and patterns of nerve hypertrophy in chronic inflammatory demyelinating polyneuropathy (CIDP), magnetic resonance neurography with 3‐dimensional reconstruction of short tau inversion recovery images was performed in 33 patients. This technique clearly showed longitudinal morphological changes from the cervical roots to the nerve trunks in the proximal arm. Nerve enlargement was detected in 88% of the patients. According to the clinical subtype of CIDP, typical CIDP patients showed symmetric and root‐dominant hypertrophy, whereas Lewis–Sumner syndrome patients had multifocal fusiform hypertrophy in the nerve trunks. The patterns of nerve hypertrophy presumably reflect the different pathophysiology of each CIDP subtype. Ann Neurol 2014.